2016
DOI: 10.1175/jcli-d-15-0472.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Solar Radiation Management on Water Cycling in a Coupled Land–Atmosphere Model*

Abstract: Solar radiation management (SRM) has been proposed as a form of geoengineering to reduce the climate effects of anthropogenic greenhouse gas emissions. Modeling studies have concluded that SRM, through a reduction in total solar irradiance by approximately 2%, roughly compensates for global mean temperature changes from a doubling of carbon dioxide concentrations. This paper examines the impact of SRM on the terrestrial hydrologic cycle using the Community Land Model, version 4, coupled to the Community Atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 121 publications
0
41
0
Order By: Relevance
“…Previous climate modeling studies have shown that globally averaged surface warming from increases in atmospheric CO 2 concentration can be roughly compensated by spatially uniform reductions in the solar constant (Caldeira & Wood, ; Kravitz, Caldeira, et al, ). Similar studies have shown that this compensation also leads to a decrease in global annual mean precipitation (e.g., Bala et al, ; Dagon & Schrag, ; Kravitz, Rasch, et al, ; McCusker et al, ; Niemeier et al, ; Ricke et al, ; Tilmes et al, ). This phenomenon has been observed following large volcanic eruptions, when aerosol surface cooling reduces the latent heat flux of water vapor to the atmosphere and weakens the global hydrologic cycle (Gillett et al, ; Iles et al, ; Trenberth & Dai, ).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Previous climate modeling studies have shown that globally averaged surface warming from increases in atmospheric CO 2 concentration can be roughly compensated by spatially uniform reductions in the solar constant (Caldeira & Wood, ; Kravitz, Caldeira, et al, ). Similar studies have shown that this compensation also leads to a decrease in global annual mean precipitation (e.g., Bala et al, ; Dagon & Schrag, ; Kravitz, Rasch, et al, ; McCusker et al, ; Niemeier et al, ; Ricke et al, ; Tilmes et al, ). This phenomenon has been observed following large volcanic eruptions, when aerosol surface cooling reduces the latent heat flux of water vapor to the atmosphere and weakens the global hydrologic cycle (Gillett et al, ; Iles et al, ; Trenberth & Dai, ).…”
Section: Introductionmentioning
confidence: 70%
“…Changes in shortwave forcing such as solar variability or volcanic eruptions have also been shown to be more effective in driving precipitation changes than the equivalent CO 2 forcing (Allen & Ingram, ; O'Gorman et al, ). Evaporation is expected to decrease under solar geoengineering because latent heat flux will respond more strongly to changes in shortwave radiation than changes in longwave radiation (Andrews et al, ; Bala et al, ; Cao et al, ; Curry et al, ; Dagon & Schrag, ; Kleidon & Renner, ; Tilmes et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar radiation that reaches the Earth surface (R s ) (also known as global solar radiation) plays a key role in various natural processes such as the hydrological cycle (Wild et al, 2005;Xia et al, 2006;Wild, 2009;Dagon and Schrag, 2016;Manara et al, 2016;Jahani et al, 2017). For example, R s provides the energy for photosynthesis, evaporation, evapotranspiration, cloud formation, snow melt, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, R s provides the energy for photosynthesis, evaporation, evapotranspiration, cloud formation, snow melt, etc. (Kun et al, 2006;Wild et al, 2015a;Dagon and Schrag, 2016;Huber et al, 2016). Therefore, it is considered as one of the most important inputs of hydrological, irrigation scheduling and crop growth models (Aladenola and Madramootoo, 2014;Jahani et al, 2016;Jahani et al, 2017;Quej et al, 2017;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%